A study of comparison on knowledge and misconceptions about hiv/aids among students in a private university in Malaysia - Mohammad Nazmul Hasan, Maziz; Md Fazlul, Karim Khan; S., Deepthi; Farzana, Y.; Munirah, B.; A., Najnin; Chakravarthi, Srikumar (Malaysian Public Health Physicians’ Association, 2019)
This descriptive cross-sectional study is aimedat studying the comparison on knowledge and misconceptions about HIV/AIDS among the Malaysian undergraduate students atSEGi University, Kota Damansara, Malaysia. Data was collectedfrom a stratified random sample of 180 students using a validated questionnaire survey which included a socio-demographics section and four sub-sections of 36 questions which assessed the general knowledge, general public perceptions, the respondent’s views on the measures to prevent the disease and misconceptions related to the disease. The data were analysedby using the SPSS software, andChi-square test was used to find the p-value for each of the questions. The average mean score assessing the knowledge of the Malaysian students in SEGi was 81.48%, where the Health Science students scored 44.31% with a standard deviation of 0.015 and the Non-Health Science students scored 37.17% with a standard deviation of 0.036. When comparing each question using the Chi-square test, most of the answers of the Health Science students and Non-Health Science students showed a significant difference where the p-value was <0.05. From the results of this study it is clear that the Health Science students had better knowledge and fewer misconceptionsabout HIV/AIDS than the Non-Health Science students. Thus, more emphasis should be directedtowardraising awareness and eliminating misconceptionsamong the Non-Health Science students.